Mortalidad por Aborto Séptico en el Hospital de Apoyo III Integrado IPSS -Tarapoto 1967 - 1987 - Yumbato Pinto, María Elena (1991)
This retrospective study of mortality Septic Abortion Support Hospital, III Integrated IPSS - Tarapoto, period 1967 - 1987; It was conducted at the Department of information and statistics that hospital, relying on statistical records, hospital clinics and historical case study records. We found that the death rate from septic abortion was 34.13 per ten thousand abortions. The direct cause of death was attributed to septic or 83.63% 16.6% abortion and septic abortion and uterine perforation. Of the 12 cases of deaths from septic abortion, 58.3% died in less than 24 hours, 16.6% died between 1 and 7 days and 24.9% last 7 days of hospitalization. 50% of these patients in the embryonic stage encontrabanse, while 33.3% in the fetal stage, no recorded cases of ovulation stage in gestation. The average age of patients was 28.3 years, ranging between 17 and 39 years; recorded an average of 3.8 pregnancies with ranging from 1-8 pregnancies. 66.6% of deceased patients came from rural areas and 83.3% were dedicated only to the work from home